TECHNOLOGIES FOR DEVELOPING STUDENTS' COMPETENCE IN FRACTAL GRAPHICS (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article describes the structure and possibility of developing students' competence in fractal graphics.  Also, in this article, a method of using the proposed structure is proposed.